2010
DOI: 10.1016/j.bcp.2009.10.022
|View full text |Cite
|
Sign up to set email alerts
|

AMPK-independent down-regulation of cFLIP and sensitization to TRAIL-induced apoptosis by AMPK activators

Abstract: The tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a TNF superfamily member that is being considered as a new strategy in anticancer therapy because of its ability to induce apoptosis, alone or in combination with other stimuli, in many cancer cells. AMPactivated protein kinase (AMPK) is an evolutionarily conserved key regulator of cellular energy homeostasis that protects the cell from energy depletion and stress by activating several biochemical pathways that lead to the conservation, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…This view is supported by our findings: (a) suppression of AMPK expression with its siRNA did not increase compound C-induced sensitization to TRAIL-mediated apoptosis; (b) transduction of DN-AMPK failed to increase in TRAIL-induced apoptosis through the AMPK inhibition. Recently, it have been reported that potent AMPK activator such as AICAR or the small molecule activator A-769662, enhances death receptor-triggered formation of death-inducing signaling complex and markedly sensitizes tumor cells to death receptor-mediated apoptosis [10,23]. Contrastingly with their reports, we demonstrate that pretreatment of human renal cancer cells with AMPK inhibitor compound C promotes the activation by TRAIL.…”
Section: Discussioncontrasting
confidence: 85%
“…This view is supported by our findings: (a) suppression of AMPK expression with its siRNA did not increase compound C-induced sensitization to TRAIL-mediated apoptosis; (b) transduction of DN-AMPK failed to increase in TRAIL-induced apoptosis through the AMPK inhibition. Recently, it have been reported that potent AMPK activator such as AICAR or the small molecule activator A-769662, enhances death receptor-triggered formation of death-inducing signaling complex and markedly sensitizes tumor cells to death receptor-mediated apoptosis [10,23]. Contrastingly with their reports, we demonstrate that pretreatment of human renal cancer cells with AMPK inhibitor compound C promotes the activation by TRAIL.…”
Section: Discussioncontrasting
confidence: 85%
“…Another mechanism which is involved in sensitization to TRAIL-induced apoptosis is downregulation of cFLIP and Mcl1. cFLIP is the major protein that prevents caspase-8 from activation by death receptors through binding to FADD and/or caspase-8 and TRAIL receptor DR5 in a ligand-dependent and -independent manner and forms an apoptosis inhibitory complex (AIC), then prevents death-inducing signaling complex (DISC) formation and subsequently suppress the activation of caspase cascade (46)(47)(48)(49)(50)(51)(52)(53). Mcl1 is an antiapoptotic protein involved in death receptor mediated pathway crosslink to mitochondrial mediated pathway by interacting with truncated Bid (tBid) and then strongly inhibits tBid-induced cytochrome c release in mitochondrial mediated apoptosis pathway (54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to XIAP, the antiapoptotic caspase-8 homolog cFLIP has previously been reported to block apoptosis induced by ligand binding to Fas, TRAIL, TNF, and CD95 receptors (14,32,33). Inhibition or downregulation of cFLIP in certain contexts is able to sensitize resistant cells to TRAIL-induced apoptosis (34)(35)(36)(37)(38)(39). In the current study, although cFLIP protein levels decreased significantly in TRAIL-or embelin þ TRAIL-treated parental SUM149 cells undergoing cell death, cFLIP levels remained unchanged in embelin þ TRAIL-treated XIAP-overexpressing cells that were also undergoing apoptosis.…”
Section: Discussionmentioning
confidence: 99%